A Barremian-?Aptian Tethyan precursor of the Cretaceous marine flooding of Morocco: Evidence from the red-bed series within the "Marginal Folds" of the eastern High Atlas. (March 2019) - Haddoumi, Hamid; Charrière, André; Feist, Monique; Baidder, Lahssen; Ferrière, Jacky; Karim, Mounir; Ettachfini, El Mostafa; Mamoun, Sidi Mohamed; Chennouf, Rachid; Rachdi, Abdelmalek; Adardor, Said
Abstract: Stratigraphic, sedimentologic, and micropaleontologic studies have been undertaken on the "Infra-Cenomanian" continental red beds (= Dekkar Group) located on the northern side of the Moroccan eastern High Atlas. Rich charophyte assemblages containing Sphaerochara magna, Ascidiella stellata, Hemiclavator sp. A, Globator trochiliscoides, Atopochara trivolvis, At. triquetra, and Flabellochara harrisii indicate a late Barremian age for the lower part of the series. Within the continental deposits we have discovered in the Middle Member of the Dekkar 2 Formation limestones and marls containing echinoderms, dasycladacean algae and foraminifera (miliolids, Ammobaculites sp., Choffatella decipiens ). The existence of two littoral to lagoonal-marine intercalations within the continental sedimentation reveals marine transgressive events during the late Barremian–?early Aptian. The lateral extension of these marine sediments allows the erection of paleogeographic boundaries that define a « Marginal Folds Gulf » characterized mainly by restricted marine paleoenvironments. This E-W directed gulf is a relatively long depression, a few tens of kilometers wide and one hundred kilometers long, developed in an area which is now at the foot of the eastern High Atlas. The infilling deposits is dominantly controlled by the distance from the North High Atlas Fault. The gulf terminated westward and probably opened northeastward into the Tethyan domain. This narrow gulf was separated from both the Tethyan Gulf known in the Central Middle Atlas during the Aptian and the coeval Atlantic Gulf located on the northern side of the Marrakech and Central High Atlas. Thus, the « Marginal Folds Gulf » is a new paleogeographic feature that documents marine incursions within the Jurassic–Early Cretaceous continental areas of the NW Africa.